Rancang Bangun Mekanisme Load Sharing Pada Link Aggregation Menggunakan Software Defined Networking - Samuel Samuel; Cahyo Eko Samudera (Faculty of Engineering and Informatics, Universitas Multimedia Nusantara, 2017)
Given the level of activity of Internet users is high on lately. Impact on the growing needs for server throughput can be treated with load sharing on link aggregation. However, it possess a problem for UDP protocol data packets which will experience jitter and packet received out of order high. Therefore, the author tries to create an algorithm to share the package which will be sent to the server with weighted round robin method that focuses UDP Protocol data packets. The author uses the Software Defined Networking (SDN) and OpenFlow protocol that is capable of directly reprogrammed network devices. Host connect by sending packets Internet Control Message Protocol (ICMP), Transport Control Protocol (TCP) and User Datagram Protocol (UDP) to the server, then do an analysis of the bandwidth, jitter, datagrams, and retry. The author has successfully implemented with the emulator Mininet and testing. The results indicate that the average jitter is able to be reduced to 50% and packets received out of order is reduced to 0 compared to standard link aggregation with weighted round robin load sharing method. Keywords— Software Defined Netwoking, Link Aggregation, Weighted Round Robin, UDP